Acquaintance with the novel "Zine El Barakat" by Gamal El Ghitani | التعرف لرواية ”زيني البركات“ لجمال الغيطاني - Herly Ramadani (Al-Zahra : Journal for Islamic and Arabic Studies, 2017)
The purpose of this research is to know what is meant by the sociology ofliterature, personality of Gamal al-Ghitani and his novel "Zaini al-Barakat", andt the social problems in the novel. In this research I used the method of libraryresearch, where I collected the evidence related to this research and then makean analyses on it. It also relied on the descriptive approach in which I describedthe events of the novel from the sociological views. I concluded severalconclusion. First, sociology of literature is the curriculum that aims at the text andits relation to the place and society in which it intervenes and shows it with asocial character. Second, Gamal Al-Ghitani is a great Egyptian writer of the sixtiesgeneration. His novel "Zaini al-Barakat" is one of the great novels in the Arab andinternational literary scene. It revolves around a person called "Zaini al-Barakat"Mamluks. Thirdly, the social problems described in his account are the crimescommitted by some princes, namely abuse of office, torture of prisoners,kidnapping and monopolization of goods, violations of social norms and war.